2018
DOI: 10.1007/s10701-018-0148-1
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Theories and Changing Hamiltonian Observables in General Relativity

Abstract: Change and local spatial variation are missing in Hamiltonian general relativity according to the most common definition of observables as having 0 Poisson bracket with all first-class constraints.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 56 publications
(93 reference statements)
0
18
0
Order By: Relevance
“…section 2.2) was established. The will become clear in the next section, where we show how the non-relativistic limit of the gauge-invariant transition amplitude leads precisely to the factorisation (67). We already know a solution to the "background" Hamilton-Jacobi equation (68).…”
Section: The Semiclassical Approach To the Problem Of Time Wkb Timementioning
confidence: 88%
See 1 more Smart Citation
“…section 2.2) was established. The will become clear in the next section, where we show how the non-relativistic limit of the gauge-invariant transition amplitude leads precisely to the factorisation (67). We already know a solution to the "background" Hamilton-Jacobi equation (68).…”
Section: The Semiclassical Approach To the Problem Of Time Wkb Timementioning
confidence: 88%
“…Under reparametrisations of the worldline, the components of tensors transform covariantly. In fact, there is no problem in defining physical quantities (observables) to be covariant rather than invariant under worldline reparametrisations (see the discussions in [66][67][68] as well as in [69,70]). Thus, we can define observables to be worldline tensors.…”
Section: Observablesmentioning
confidence: 99%
“…Since c. 1980 a reforming literature has aimed to recover spatio-temporal coordinate freedom in GR and mathematical equivalence between the Hamiltonian and Lagrangian formulations (e.g., [13,[19][20][21][22][23][24][25][26][27][28][29]). Recently it was shown how to bootstrap a definition of observables using equivalent formulations of massive theories, one without gauge freedom (so everything is observable) and one with gauge freedom [17,35]. It turns out that observables are basically tensor fields (or more generally geometric objects [36][37][38] including connections or any set of components with a coordinate transformation rule) that are invariant under any internal gauge symmetries present [39]; thus observables are merely covariant, not invariant, under coordinate transformations.…”
Section: Hamiltonian Change Seems Missing But Lagrangian Change Is Notmentioning
confidence: 99%
“…Using the principle that equivalent theories (or theory formulations) should have equivalent observables, I argued that observables in GR should be invariant under internal gauge symmetries (which is not novel) but only covariant under coordinate transformations, so observables are basically geometric objects, or tensor calculus all over again, such as g and its concomitants [17,35,39]. The nonlinear group realization formalism comes very close to including spinors as part of a geometric object along with the metric (or its conformal part).…”
Section: Observables In Einstein-dirac Theorymentioning
confidence: 99%
“…Recently the author showed that for massive electromagnetism, the requirement that equivalent theories have equivalent observables (in other words, that gauge-fixing/un-fixing doesn't change the observable content) is inconsistent with the separate first-class constraint view but fits perfectly with the gauge generator G [47,48]. Massive electromagnetism approaches massless (Maxwell) as m → 0, whether classically or in quantum field theory [5,24,44].…”
Section: Observables Reformed With the Gauge Generator Gmentioning
confidence: 99%